Gemstones - Dayton, Connor (New York : PowerKids Press, 2007)
Explores gemstones, explaining what they are, how they are classified, where they are found, what makes them shine, and their uses; and describing precious, semiprecious, organic, and synthetic varieties. Includes a glossary and a list of related Internet sites.
What are gemstones? -- Classifying gemstones -- How are gemstones made? -- Getting gemstones -- Making them shine -- Precious gemstones -- Semiprecious gemstones -- Organic gemstones -- Synthetic gemstones -- Using gemstones.
Includes index.
2.7
K-3
Keywords: Precious stones -- Juvenile literature; Precious stones; Precious stones; Precious stones